Plan De Mejoramiento Logístico De Domicilios De Sandwich Gourmet En La Ciudad De Bogotá (2023)
Fast food sales in Bogota have increased considerably in recent years, largely due to the growing demand for home delivery services. In this situation, home delivery has become a crucial success factor for the industry.